The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/sj.bdj.2016.854
|View full text |Cite
|
Sign up to set email alerts
|

The risks and benefits of social media in dental foundation training

Abstract: The use of social media has greatly expanded in the last decade, with widespread use of smartphones, the internet, and other multimedia to enhance learning. There is evidence to suggest that social media has a place in healthcare education, but there is limited research to suggest the effectiveness or use of it in dental foundation training. This paper discusses the risks and benefits of social media and suggests that a better understanding of social media and its role in the development and practice of newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…During the last decade, due to widespread use of smartphones, the Internet, and smart devices, the use of social media has greatly increased, has gained popularity, and has enhanced learning among students. [1][2][3][4][5] Social media applications such as Facebook, Twitter, Google+, LinkedIn, and Student Doctor network allow users to connect, collaborate, and communicate with one another on a global scale. [1][2][3][4][5] In 2015, it was reported that 88% of 16-24-year-olds used social media daily, compared to 60% aged 65 and older, which supports the ever-increasing popularity of social media.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, due to widespread use of smartphones, the Internet, and smart devices, the use of social media has greatly increased, has gained popularity, and has enhanced learning among students. [1][2][3][4][5] Social media applications such as Facebook, Twitter, Google+, LinkedIn, and Student Doctor network allow users to connect, collaborate, and communicate with one another on a global scale. [1][2][3][4][5] In 2015, it was reported that 88% of 16-24-year-olds used social media daily, compared to 60% aged 65 and older, which supports the ever-increasing popularity of social media.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Social media applications such as Facebook, Twitter, Google+, LinkedIn, and Student Doctor network allow users to connect, collaborate, and communicate with one another on a global scale. [1][2][3][4][5] In 2015, it was reported that 88% of 16-24-year-olds used social media daily, compared to 60% aged 65 and older, which supports the ever-increasing popularity of social media. 2 Students are digitally literate, social, team-workers, both visual and interactive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 14 In fact, there is an ongoing debate within the BDJ on the impact and significance of social media on dentistry and dental professionalism. [15][16][17][18][19][20][21] While a lot of research has been conducted on the online behaviours of medical and allied health professional students (see above), less has been undertaken on dental students, except for Kenny and Johnson 22 and Nason et al 23 Mindful of this gap in our knowledge, this research was conducted to explore the social media habits of dental students and their views on e-professionalism. Its aim was to determine whether students were aware of the standards set by the GDC regarding social media and whether they believed they were being professional in their online activities.…”
Section: Introductionmentioning
confidence: 99%
“…39 In fact, it is difficult to verify the authenticity of the information presented on social media websites. 40 In addition, information is usually lacking referencing, incomplete or being informal. 41 Thus, it is the user's responsibility to verify the reliability and the quality of the information.…”
Section: (61)mentioning
confidence: 99%